أقلمة الصراع في اليمن:دراسة في الأطراف والأطماع - الفقية ., أحمد (University of Eloued جامعة الوادي, 2022)
تهدف هده الدراسة إلى البحث في الأسباب الحقيقية للأزمة اليمنية والتي حوّلت الحراك السياسي والاجتماعي في اليمن( يمني- يمني) إلى أزمة دولية متعدّدة الفواعل ومتشابكة المصالح صعب إيجاد حل لها.وذلك من خلال توضيح الغموض بشأن التدخلات الإقليمية لكل من الإيرانية، السعودية والإماراتية الأطراف الذين لهم الحضور البارز والدور المؤثر في هذا الصراع،بالإضافة إلى محاولة الوقوف على خلفية وحقيقة أطماع هذه التدخلات من خلال تسليط الضوء على الآليات والوسائل التي تمّ اعتمدتها الأطراف الثلاث لإثبات شرعيتهم للتدخل في الشأن اليمني . فرغم تباين اِستراتيجيات التدخلات الإقليمية في اليمن بين التدخلات المباشرة وغير المباشرة وبين العسكرية والإيدلوجية والسياسية غير أن أهدافهم كانت وإلى حد بعيد متشابهة تمثلت في محاولة تحقيق موطئ قدم في المنطقة، بغرض تنفيذ المشاريع الاِقتصادية والتوسعية بهدف الوصول إلى المكانة الإقليمية في المنطقة . This study aims to examine the real causes of the Yemeni crisis, which transformed the political and social movement in Yemen (Yemeni-Yemeni) into an international crisis with multiple actors and intertwined interests, which is difficult to find a solution to. This is by clarifying the ambiguity regarding the regional interference of the Iranian, Saudi and Emirati parties who have a prominent presence and an influential role in this conflict, in addition to trying to identify the background and reality of the ambitions of these interventions by highlighting the mechanisms and means adopted by the three parties to prove their legitimacy to intervene in the conflict of the Yemeni issue Despite the different strategies of regional interventions in Yemen between direct and indirect interventions and between military, ideological and political interventions, their goals were to a large extent similar, represented in an attempt to achieve a foothold in the region, with the aim of implementing economic and expansion projects with the aim of reaching a regional position in the region.
المجلد13 العدد2
Keywords: اليمن ؛الصراع اليمني ؛الأطماع الإقليمية ؛ إيران؛ السعودية؛ الإمارات; Yemen ; Yemeni conflict ; regional ambitions ; Iran ; Saudi Arabia ; UAE